Apple phenolic extracts ameliorate lead-induced cognitive impairment and depression- and anxiety-like behavior in mice by abating oxidative stress, inflammation and apoptosis via the miR-22-3p/SIRT1 axis. Issue 5 (15th February 2022) - Ren, Yongfeng; Sun-Waterhouse, Dongxiao; Ouyang, Fangxin; Tan, Xintong; Li, Dapeng; Xu, Longhua; Li, Bo; Wang, Yongli; Li, Feng
Abstract : Lead can lead to neurotoxicity and cognitive impairment. Abstract : Lead can lead to neurotoxicity and cognitive impairment. In this study, for the first time, the protective effects and working mechanisms of apple phenolic extracts (APEs) against lead acetate (Pb(Ac)2 )-induced cognitive impairment and depression- and anxiety-like behavior were examined in vivo . Forty male mice were administered daily ( via gastric gavage; 8 weeks) with 0.9% normal saline (control), Pb(Ac)2 (20 ppm), APE (200 ppm) or Pb(Ac)2 (20 ppm) + APE (200 ppm). The APE contained five major phenolic compounds: chlorogenic acid, proanthocyanidin B2, epicatechin, phloridzin and phloretin. Behavioral tests, histopathological examinations and biochemical analyses revealed that Pb(Ac)2 -treated mice exhibited cognitive and behavioral deficits ( i.e. a reduced percentage of spontaneous alternation, prolonged duration of immobility and decreased open field test scores compared with the control. Pb(Ac)2 exposure significantly increased cellular oxidative damage and the levels of pro-inflammatory cytokines (interleukin (IL)-1β, IL-6 and tumor necrosis factor-α (TNF-α), ionized calcium binding adaptor molecule 1 (Iba1) and pro-apoptotic proteins (caspase 3, caspase 9 and Bax), while downregulating the expression of Bcl-2 in the brain. APE administration alleviated these Pb(Ac)2 -induced changes through regulating oxidative stress, neuroinflammation and apoptosis via the miR-22-3p/Sirtuin 1 (SIRT1) signaling pathway. Taken together, the APE has the potential to treat lead-induced neurotoxicity and neurodegenerative disorders via antioxidant, anti-inflammatory and anti-apoptotic actions.